2016
DOI: 10.18410/jebmh/2016/681
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study of Sensory Neural Hearing Loss in Csom With and Without Cholesteatoma

Abstract: BACKGROUNDChronic suppurative otitis media still remains a major cause of conductive hearing loss in our country. But, a few patients also display an added sensorineural hearing loss. MATERIALS & METHODSHundred patients with CSOM undergoing surgery at our department were included in the study. The affected ears formed the 'CSOM Group' and the normal ears formed the 'Control group'. Detailed otological history, clinical, surgical and audiometric findings were recorded and analysed. RESULTSIt was inferred that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…However, in relation to the BC threshold (the most essential parameter for determining SNHL), our study demonstrated that BC thresholds did not differ significantly between the CSOM with and without cholesteatoma groups (20). Detectable BC thresholds at all three frequencies did not show significant differences between the CSOM with and without cholesteatoma groups in our study; however, there were more patients with undetectable BC thresholds at all 3 frequencies in the CSOM with cholesteatoma group than the CSOM without cholesteatoma group.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…However, in relation to the BC threshold (the most essential parameter for determining SNHL), our study demonstrated that BC thresholds did not differ significantly between the CSOM with and without cholesteatoma groups (20). Detectable BC thresholds at all three frequencies did not show significant differences between the CSOM with and without cholesteatoma groups in our study; however, there were more patients with undetectable BC thresholds at all 3 frequencies in the CSOM with cholesteatoma group than the CSOM without cholesteatoma group.…”
Section: Discussioncontrasting
confidence: 64%
“…Additionally, 30 (75.00%) of the 40 affected ears had symptoms of ear discharge, 34 (85.00%) had tympanic membrane perforation, and 11 (27.50%) had sensed tinnitus. Female patients accounted for 48.72% [19] of the CSOM with cholesteatoma cohort, and male patients accounted for 51.28% [20]. The mean age of the CSOM with cholesteatoma cohort was 43.64 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations